Personal Autonomy in Plural Societies A Principle and its Paradoxes - Foblets, Marie-Claire; Graziadei, Michele; Renteln, Alison Dundes (Routledge Studies in Cultural History, 2018)
This volume addresses the exercise of personal autonomy in contemporary situations of normative pluralism. In the Western liberal tradition, from a strictly legal and theoretical perspective the social individual has the right to exercise the autonomy of his or her will. In a context of legal plurality, however, personal autonomy becomes more complicated. Can and should personal autonomy be recognized as a legal foundation for protecting a person's freedom to renounce what others view as his or her fundamental 'human rights'? This collection develops an interdisciplinary conceptual framework to address these questions and presents empirical studies examining the gap between the principle of personal autonomy and its implementation. In a context of cultural diversity, this gap manifests itself in two particular ways. First, not every culture gives the same pre-eminence to personal autonomy when examining the legal effects of an individual's acts. Second, in a society characterized by 'weak pluralism', the legal assessment of personal autonomy often favours the views of the dominant majority. In highlighting these diverse perspectives and problematizing the so-called 'guardian function' of human rights, i.e., purporting to protect weaker parties by limiting their personal autonomy in the name of gender equality, fair trial, etc., this book offers a nuanced approach to the principle of autonomy and addresses the questions of whether it can effectively be deployed in situations of internormativity and what conditions must be met in order to ensure that it is not rendered devoid of all meaning.